PENGARUH INTERNAL LOCUS OF CONTROL, KONSEP DIRI, DAN DUKUNGAN KELUARGA TERHADAP KEMATANGAN KARIR MAHASISWA PEWIRAUSAHA PADA UNIVERSITAS KUNINGAN - Iskandar, Iskandar; Mulyati, Sri; Anggraeni, Dini (Universitas Kuningan, 2022)
AbstractThe problem behind this research is the low level of career maturity of entrepreneurial students at the University of Kuningan. This can be seen from the data held by the Student Entrepreneurship Development Center (PPKM) Universitas Kuningan in 2020 which shows the low level of success of their business and the lack of clarity about the sustainability of the business they run. The theory search raises three predictor variables, namely internal locus of control, self-concept, and family support.The subjects of this research are the students of Universitas Kuningan who are